The Relevance of Muhammad Abduh's Thought in Indonesian Tafsir: Analysis of Tafsir Al-Azhar - Zulfikri Zulkarnaini; Mohammed A.F. Badawi (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2021)
In this study, the author uses the descriptive-historical approach to explain the influence of Muhammad Abduh's thoughts and Tafsir Al-Manar's coming to Indonesia. Especially in the Tafsir Al-Azhar by Hamka, who was born in the 20th century. This interpretation emerged when Indonesia was experiencing a state of transition from colonialism to independence. At the same time, modern Islamic thought became strong in Indonesia. The modern approach of Tafsir al-Manar has inspired Hamka's model of interpretation in Tafsir Al-Azhar. Here the authors find similarities in terms of methodology, namely social-community (Adab ijtima'i). Apart from that, there are some similarities and differences between the Tafsir Al-Manar with Tafsir Al-Azhar. For example, the view of the verses of